Comparison of double and triple high-dose chemotherapy with autologous blood stem cell transplantation in patients with metastatic breast cancer - Schneeweiss, Andreas; Hensel, Manfred; Goerner, Ronald; Khbeis, Tanja; Hohaus, Stefan; Egerer, Gerlinde; Solomayer, Erich-Franz; Haas, R.; Grischke, Eva-Maria; Bastert, Gunther; Ho, Anthony Dick (Stem cells, 2001)
In patients with metastatic breast cancer (MBC), early dose intensification with multiple cycles of peripheral blood stem cell-supported high-dose chemotherapy (HDCT) seems superior to a late dose-intensification strategy. We compared the progression-free survival (PFS) and overall survival (OS) of 20 patients treated with a double (D)-HDCT regimen to 20 patients who received a triple (T)-HDCT, matched by age, estrogen receptor (ER) status, adjuvant chemotherapy, initial disease-free interval, predominant metastatic site, and number of metastatic sites. At a median follow-up of 41.5 months (range, 14-88 months) an intent-to-treat analysis showed no difference in PFS (p = 0.72) and OS (p = 0.93) between the matched patients. For all 76 patients treated within the D- or T-HDCT trial, median PFS and OS was 13 months (range, 2-78 months) and 24.5 months (range, 7-78 months), respectively. In multivariate analysis independent predictors of shorter OS included negative ER (relative risk [RR] = 3.0 [95% confidence interval (CI) 1.5-5.9]; p = 0.002), more than two metastatic sites (RR = 2.4 [95% CI 1.0-5.7]; p = 0.049) and failure to achieve complete remission/no evidence of disease (CR/NED) after HDCT (RR = 4.5 [95% CI 2.0-10.1]; p < 0.0001). These data show that early dose intensification with T-HDCT is not superior to a D-HDCT regimen in patients with MBC. ER-negative tumors, more than two metastatic sites and no CR/NED after HDCT, are associated with inferior outcome.
Elektronische Reproduktion der Druckausgabe
Gesehen am 21.12.2021